2015
DOI: 10.1007/s13193-015-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Rare Small Bowel Tumor in a Child and Review of Literature

Abstract: A two and half years old female child presented with recurrent episodes of colicky abdominal pain and bilious vomiting since 3 months. On clinical examination, a small mobile intra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Imaging usually demonstrates a hypoechoic or hypoattenuating lesion which may be hypervascular with or without calcifications (Fig. 1) (1,2,4,6,8,10,12,13). When found endoscopically appearances are typically sessile and polypoid (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Imaging usually demonstrates a hypoechoic or hypoattenuating lesion which may be hypervascular with or without calcifications (Fig. 1) (1,2,4,6,8,10,12,13). When found endoscopically appearances are typically sessile and polypoid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that these lesions may result from disordered inflammation. Postulated triggers include infections, previous surgery, inflammatory and autoimmune conditions, however the only relevant contributing past medical history was found in two patients with Wilms tumour and H pylori gastritis (8,13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations